Pakatan Harapan’s first year in Putrajaya: reform and resistance - Muhamad Nadzri Mohamed Noor, (Penerbit Universiti Kebangsaan Malaysia, 2021)
On 9 May 2018, the longstanding ruling regime in Malaysia, the Barisan Nasional (the National Front, BN), suffered its first loss in the 14th General Election (GE14) to the Pakatan Harapan (the Alliance of Hope, PH) despite its heavy use of authoritarian measures. In the subsequent months, a number of reforms were made largely by changing the heads of key government agencies apart from reviewing the role of those agencies towards the process of democratisation. Although the standard of reforms in Malaysia during the first year of PH’s rule was arguably a small scale restructuring, it has attracted a substantial amount of resistance from certain quarters – from within and outside the new ruling party. This article contends that the reform projects implemented by the Mahathir-led PH government during its first year in Putrajaya was somewhat constrained by structural characteristics of the new ruling party alongside the current reality of the Malaysian economy and its society. For these reasons, the objective of this article is two-fold. Firstly, it makes a concise survey of the reform projects that have been implemented by PH government between mid-2018 to mid-2019. Secondly, it identifies the sources of resistance that have significantly constrained the potential for a fuller level of democratisation in the Mahathir-led PH government.